The Factors Affecting The Occurrence of Obesity in College Students - Tjie Kok; Vanessa Wiriantono; Lisa Aditama; Jordan Bakhriansyah (Unnes Journal of Public Health, 2023)
Obesity is a physical condition that can lead to health disorder. An increase in body mass index can be a risk factor for some non-communicable diseases, among which are cardiovascular diseases. College students are among the people with high risk of obesity. This review aims to describe factors that can cause obesity and hence the increasing risk of cardiovascular diseases in college students. We first collected 608 studies associated with our review and then selected 9 studies that highly correlate to our specific purpose. We evaluated each selected study for its quality and risk of bias using STROBE. We then conducted data extraction of each study. It can be concluded from the results of data extraction that even though there are various factors contributing to the occurence of obesity in college students, skipping breakfast and high snack consumption have a close relationship with the occurence. In addition, inadequate physical activity and high calorie diet also contribute to its occurence. Finally, smoking is also associated with the occurence of obesity, that can lead to the increasing risk of cardiovascular diseases.